Komposisi Verbal Dalam Koran Jawa Pos Bulan Juli 2017 - Heny Sulistyowati (STKIP PGRI Jombang, 2017)
Composition was one of accidence process that conected two morfem or more, so make new meaning. Composition process have form development based on word grade construction, it is noun composition, verb composition and adjectival composition. Verb composition is verb category of clausa unit on compostion. The research problem were verb composition have equivalent meaning connection, antipodes, and synonim between complex word formation. The object used in this study was Jawa Pos July 2017. Jawa Pos is weekly newspaper as major reference for take decision and Indonesian public in Indonesia. The title was Komposisi Verbal Dalam Koran Jawa Pos bulan Juli 2017 the usage of verb compotion with the aim search verbal compostion form wich have equivalent meaning connection, antipodes, and synonym between complex word formation.. Methode used in this study is descriptive qualitative because try to descripe verb composition form wich have equivalent meaning connection, antipodes and synonym between compley word formation. The research do with make a note of word that included in verbal compostion word on the tabel based on research problem. Verb composition with meaning connection synonym complex formation the researces found diam tercengang dan melonjak tinggi. Base element on verbal composyion form is verb + verb (V + V), verb + noun (V + N), and verb + adjective (V + Adj).